DESARROLLO Y EVALUACIÓN DE LOS PROCESOS DE RAZONAMIENTO COMPLEJO EN CIENCIAS - Cárdenas Salgado, Fidel Antonio (Tecné, Episteme y Didaxis: TED, 1998)
Despite the enhanced importance given by science educators and researchers to evaluation in sciences in the past, the search for better and more reliable assessing processes is nowadays a research priority. Although the areas of science to be assessed have been generally accepted as including knowledge of concepts and facts, process skills, science thinking, problemsolving skills, abilities reeded to manipulate laboratoty equipment and the disposition of students to apply scientific knowledge, the impact of assessment on students, teachers and parents has not been overlooked. However, advances in cognitive psychology, science education and research on assessment on science are calling for new dimensions, such as complex reasoning, to be researched in the field. Complex reasoning is a competence included as a desirable outcome of Science education in many Science curricula and is characterized by the following attributes: problem-solving, decision-making and critical and creative thinking. This paper presents a theoretical framework fon assessment in science involving the development of competencies through science education and emphasizes complex reasoning. A working model to categorize assessment tasks in complex reasoning is described and some of the main questions to be researched in the une are stated. The need for interdisciplinary work as well as close interaction with other unes of investigation has also been put forward. It is the main objective of this line of nesearch to explore and propose more systematic assessment processes in science education to trace the evolution of students understandings and achievements mainly in secondary schools.